The Pyramid of Values: Value-based Leadership Lessons from the Bhagavad Gita - Nanjundappa S Harshavardhana; Kuravanka G Srinivas (Dr. Chinmay Pandya, 2021)
The Bhagavad Gita (BG) is studied from spiritual, theological and religious perspective. It is a collection of 700 verses wherein beset by compassion and grief, Arjuna loses the will to fight and has a nervous breakdown. The supreme lord Srikrishna's preachings by which he convincingly manages to motivate Arjuna to fight his enemies with determination constitutes the gist the BG. It is considered as 'India's book of Answers' to all the problems of human civilization and has inspired generations over thousands of years. Srikrishna preaches three-fold path of: i) Action (Karma); ii) Devotion (Bhakti) and iii) Knowledge / Intellect (Jnana) emphasizing that the greatest battles are fought in one's own mind. Wisdom from the BG is increasingly recognized in the field of leadership and management. It emphasizes that the core of leadership lies in one's character and is influenced by 'Value' systems and combination of three key 'Personality' traits. A good leader should cultivate 'Sattvic' virtues and act selflessly for greater good of all with judicious use of power that comes with authority. The principle leadership lessons taught by BG are: i) To know thyself; ii) Practice renunciation by selfless service; iii) Fearless action with integrity; iv) Embrace formidable challenges with a  prepared mind to face them and v) Moral righteousness. The BG recommends one to approach leadership role with an attitude as a custodian who protects and motivates his team by practising the art of 'Active Listening'. Incorporating the teachings of BG would facilitate a leader to be free of bias, observe equanimity and make wise decisions leading to contentment and inner peace.